g en erated num ber if it is g en erated in every base. F o r exam ple, 2 , 10, 14, 2 2 , 3 8 , etc. are univer-sal g en erated n u m b ers. T h e num...

0 downloads 6 Views 692KB Size

No documents

1. INTRODUCTION In 1963, D. R. Kaprekar [1] introduced the concept of self-numbers. Let k>\ trary integer. A natural number m is said to be a £-self-number iff the equation

be an arbi-

m-nJrdk(ri) has no solution in an integer n > 0, where dk(n) denotes the sum of digits of n while represented in the base k. Otherwise, we say that m is a ^-generated number. And m is said to be a universal generated number if it is generated in every base. For example, 2, 10, 14, 22, 38, etc. are universal generated numbers. The number 12 is 4-generated by 9, but it is a 6-self-number. In 1973, V. S. Joshi [2] proved that "if k is odd, then m is a &-self-number iff m is odd," i.e., every even number in an odd base is a generated number. In 1991, R. B. Patel ([3], M.R. 93b: 11011) tested for self-numbers in an even base k. What he proved is: 2ki, 4£ + 2, k2 +2k + \ are ^-self-numbers in every even base k > 4. In the present paper, we first prove some new results on self-numbers in an even base k. Theorem 1: Suppose m = b0+blk, 0

0

2\k,

k>4.

Then m is a &-self-number iff bQ - bx = -2. In particular, 2k, 3& + 1, 4£ + 2, 5£ + 3, etc. are ^-self-numbers. Theorem 2: Suppose m = b0+blk+b2k2,

0

0

0

2\k,

k>4.

Then m is a &-self-number iff b0, bh and b2 satisfy one of the following conditions: b{ = 0, bQ-bxb2 = -4 or k-3; bx = l, \ - \ - b 2 =-2 or - 4 ; b-x-2 or3, i 0 - 6 1 - i 2 = - 2 ; bx>4, bQ~bl-b2 = -2 or - k - 3. In particular, k2 +k, k2 +2k + l, k2 + 3k + 2, 2k2 +A + 1, 2k2 +2k + 2, 3k2 +k + 2, 5k2 + l (k > 6), 4k2 + * +1 (£ > 6), 5^ 2 -k

(k> 6), £ 3 - A:2 + 4k, etc. are £ self-numbers.

Secondly, we study the number G(x) of universal generated numbers rn

* Project supported by NNSFC and NSF of Zhejiang Province. 144

[MAY

ON k -SELF-NUMBERS AND UNIVERSAL GENERATED NUMBERS

2, PROOF OF THEOREM 1 If possible, let m be ^-generated by some w, where t

n = ^atk\

Q^c*i

0

Then t

4 W

r

t

I ^ /=o

and

m = w +rfJk(w)= ^ a r . ( * / + l). /=o

Since m = b0+bxk

(1)

0 < i < 2.

(A) If i = 0, then (1) holds iff b0 -bx > 0 is even; (B) If i = 1, then (1) holds iff bQ - bx < k - 3 is odd; (C) If i = 2, then (1) holds iff ^ - ^ < - 4 is even. Hence, m is a A>self-number iff b0-bx = - 2 o r k - 1 . This completes the proof of Theorem 1.

The latter is impossible because b0<

k-\.

3, PROOF OF THEOREM 2 If possible, let m be ^-generated by some n. As in the proof of Theorem 1, we have b0+bxk + b2k2 = 2aQ+ax(k + l) + a2(k2 +1), with b2-\

(2)

Case I. a2-b2.

From (2), we see that ax

Taking ax=bx-

j , j > 0, we have

+j(k +1) = 2a 0 .

(3)

Noting that 0 < a0 < k, one has: (A) If y = 0, then (3) holds iff bQ - b x - b 2 > 0 is even; (B) If jf = 1, then (3) holds iff b0 - bx - b2 > -k - 1 is odd and bx > 1; (C) If jf = 2, then (3) holds iff b0-bx-b2< (D) If 7 - 3, then (3) holds \ffbQ-bx-b2

- 4 is even and bx>2\

odd and bx > 3;

.(E) If j > 4, then (3) never holds. Case II. a2 = b2 - 1 . Taking ax = k-j,

j > 1, it follows from (2) that

( 6 1 + y - l ) £ = 2 a 0 - y - l + 62-Z>0 or b0-h2 + (bl+j-l)k Since 2a0 -j-l+b2

1996]

= 2*0.

(4)

-b0 < 3 ( & - l ) , one has ^ 4 - j - l < 2. Noting that 0 < a 0 < £ - l , one has:

f

If ^ = 0, j = 1, then (4) holds iff 60 - 62 > - 2 is even;

f

ifbl = 0J = 2, then (4) holds iff b0 -b2 < k - 5 is odd;

(A) (B)

+ j-l

145

ON k -SELF-NUMBERS AND UNIVERSAL GENERATED NUMBERS

(C)' If bx = 0, j = 3, then (4) holds iff bQ - b2 < -6 is even; (D)' lfb1 = l,j = l, then (4) holds iff b0 - b2 < k - 4 is even; (E)' If Aj = 1, y = 2, then (4) holds iff Z>0 - 62 < -5 is odd; (F) If^ = 2, 7 = 1, then (4) holds iff b0-b2 < -4 is even; (G) If ^ > 3, then (4) never holds. Thus, (A)', (B)', and (C)' together imply that if \ = 0, (4) does not hold iff b0-b2 = -4 or k-3, i.e., b0 -bx -b2 = -4 o r k - 3 . According to Case I, (2) has no solution iff b0-b1-b2= - 4 or k - 3. If b{ = 1, (D)' and (E)' together imply that (4) does not hold iff b0-b2>k-4 ork-4> bQ-b2>-5 is odd, i.e., bQ -bx -b2 > k o r k - 5 > b 0 - \ -b2 > -6 is even. According to Case I, (2) has no solution iff bQ - bx - b2 = -2 or - 4. If bx = 2, then from (F) (4) does not hold iff b0-b2> -4 or is odd, i.e., b0-bl-b2> -6 or is odd. According to Case I, (2) has no solution iff b0-b1-b2 = '-2. If Z>!>3, (4) never holds. According to Case I, (2) has no solution iff bQ-bx-b2 ~-2 or -k-3. For the latter, bx > 4. This completes the proof of Theorem 2. 4. PROOF OF THEOREM 3 Let fs(n) denote 2 ^ + 2* - 1 -2, where s> 1

£ l<2 J «+2 i " _ 1 -2

1 <£min{2*- 2 ,x/2*}< s^l

£ j<(l/2)log 2 JC+l

2s'2 +

£

x/T <2

^>(l/2)log 2 x+l

This completes the proof of Theorem 3. ACKNOWLEDGMENT The author is grateful to the referee for many useful comments and valuable suggestions. REFERENCES 1. D. R. Kaprekar. 77?e Mathematics oj'New Self-Number, pp. 19-20. Devalali, 1963. 2. V. S. Joshi. Ph.D. Dissertation, Gujarat University, Ahmedadad, October 1973. 3. R. B. Patel. "Some Tests for ^-Self-Numbers." The Mathematics Student 56.1-4 (1991): 206-10 (M.R.93b: 11011). AMS Classification Number: 11A63

146

[MAY